2019
DOI: 10.1016/j.jvscit.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The utility of adjunctive electroencephalography while performing transcarotid artery revascularization

Abstract: Transcarotid artery revascularization (TCAR) has been used as an alternative to carotid endarterectomy and transfemoral carotid artery stenting. Although TCAR has been associated with a decrease in perioperative strokes compared with transfemoral carotid artery stenting, little is known about the safety of cerebral blood during flow reversal or the value of adjunctive electroencephalography (EEG) monitoring in performing TCAR. We describe two cases of EEG changes in patients undergoing TCAR. These cases highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our group have previously described two patients undergoing TCAR, demonstrating neuromonitoring changes during active flow reversal. 2 These cases were managed by the use of low-flow reversal around the time of stent placement, during which a brief period of high-flow was tolerated. We have previously suggested that neuromonitoring might be used as an adjunct to assess for compromised collateral cerebral blood flow in patients undergoing TCAR, for example, in patients with contralateral occlusion or vertebral disease, by utilizing a brief test clamp prior to proceeding with TCAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group have previously described two patients undergoing TCAR, demonstrating neuromonitoring changes during active flow reversal. 2 These cases were managed by the use of low-flow reversal around the time of stent placement, during which a brief period of high-flow was tolerated. We have previously suggested that neuromonitoring might be used as an adjunct to assess for compromised collateral cerebral blood flow in patients undergoing TCAR, for example, in patients with contralateral occlusion or vertebral disease, by utilizing a brief test clamp prior to proceeding with TCAR.…”
Section: Discussionmentioning
confidence: 99%
“…1 Neuromonitoring in conjunction with carotid revascularization has been documented to help surgeons predict the risk of perioperative stroke. [2][3][4] Many practitioners, however, do not routinely use neuromonitoring during TCAR, citing the lack of evidence supportive of use and overall good outcomes in pivotal trials. 5,6…”
Section: Introductionmentioning
confidence: 99%